Tumor necrosis factor-α, interleukin-4 and -6 in the serum of health, chronic periodontitis, and type 2 diabetes mellitus - Anirudh Balakrishna Acharya; Srinath Thakur; Mahadevayya Veerayya Muddapur; Raghavendra Dhirendra Kulkarni (Wolters Kluwer Medknow Publications, 2016)
Background: Cytokines are significant in the development and progression of chronic periodontitis (ChP) and type 2 diabetes mellitus (DT2). Insufficient information is available regarding the pro- versus anti-inflammatory cytokines in ChP's influence on systemic levels of cytokines on DT2. This study investigated the levels of tumor necrosis factor-α (TNF-α), interleukin (IL)-4 and IL-6 in the serum of patients with ChP, DT2, and with both ChP and DT2, as compared to health. Materials and Methods: A total of eighty participants were grouped equally groups as healthy (NH), ChP with, and without DT2 (ChP and ChP + DT2) and only type 2 diabetes (DT2). Plaque and gingival indices, bleeding on probing, pocket probing depths, clinical attachment loss, were evaluated. Serum samples were collected to measure glycated hemoglobin, random blood sugar. TNF-α, IL-4 and -6 was assessed by ELISA. Results: The selected cytokines were detected in all the participants. TNF-α and IL-6 were highest in ChP + DT2 group, whereas IL-4 was highest in health. Significant differences and correlation were observed between the cytokines, periodontal, and glycemic parameters and among the four groups. Conclusion: TNF-α and IL-6 appear to heighten the inflammatory state in patients with both type 2 diabetes and periodontitis, but IL-4, though considered an anti-inflammatory mediator was not convincing in such a role in this study. The cytokine behavior needs to be studied further in larger studies.